A luta pelo poder : a política gaúcha em perspectiva (1934-1937) - Lapuente, Rafael Saraiva (2016)
This paper analyzes the Rio Grande do Sul state’s policies between 1934 and 1937, during the government of Flores da Cunha. Our research is based on two main foundations: 1. In the negotiations involving the pacification of Rio Grande’s policy, when this issue gained momentum during the 1934 elections, until the signing of the pact called modus vivendi; and 2. from the political erosion of governor Flores da Cunha base, which began in late 1936, until his resignation in 1937. We seek to know, through the political trends of the period (PRR, PL, PRL, Dissent Liberal, PRC, UDN, Liberation Action) and through the actors involved (Raul Pilla, Maurício Cardoso Flores da Cunha, Benjamin Vargas, João Neves da Fontoura, Antunes Maciel, Borges de Medeiros, Getúlio Vargas and others), how was the process that led from pacification to the definite rupture in the state's politics. For this we use a number of primary sources, especially newspapers and private collections telegrams, dealing with them according to content analysis, and also following authors who thought, theoretically and methodologically, the concept of Regional History. In addition, we put this work into the debates surrounding the nouvelle histoire politique by historiography in recent years. We developed our research through the analysis of documents of NUPERGS, CPDOC, Media Museum Hipólito José da Costa, DELFOS/PUCRS, Solar dos Câmara, Arquivo Radio Difusão/UFRGS and Rio Grande do Sul’s historical archives.